1998
DOI: 10.1002/pro.5560070403
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and structural consequences of flexible loop deletion by circular permutation in the streptavidin‐biotin system

Abstract: A circularly permuted streptavidin (CP5 1/46) has been designed to remove the flexible polypeptide loop that undergoes an open to closed conformational change when biotin is bound. The original termini have been joined by a tetrapeptide linker, and four loop residues have been removed, resulting in the creation of new N-and C-termini. Isothermal titration calorimetric studies show that the association constant has been reduced approximately six orders of magnitude below that of wild-type streptavidin to lo7 M-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 45 publications
(39 reference statements)
8
71
1
Order By: Relevance
“…This finding is consistent with a destabilization of the water ring solvating the active site due to the loss of the hydrogen binding groups maintaining it (8). Circular deletion of the mobile loop formed by residues 47-51 that hydrophobically enclose the ligand from above, most notably by Val-47, loses 8 kcal/mol lower than the unmutated protein; this is much more than continuum methods predict but in agreement with our estimate (9). Mutating Trp-79 to Phe was found to enthalpically stabilize biotin binding by 1.5 kcal/mol but entropically destabilize it by 2.4 kcal/mol (10).…”
Section: Resultssupporting
confidence: 90%
“…This finding is consistent with a destabilization of the water ring solvating the active site due to the loss of the hydrogen binding groups maintaining it (8). Circular deletion of the mobile loop formed by residues 47-51 that hydrophobically enclose the ligand from above, most notably by Val-47, loses 8 kcal/mol lower than the unmutated protein; this is much more than continuum methods predict but in agreement with our estimate (9). Mutating Trp-79 to Phe was found to enthalpically stabilize biotin binding by 1.5 kcal/mol but entropically destabilize it by 2.4 kcal/mol (10).…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the water channel is lined by residues of the ordered loop 2, which can aid the channel to act as a proton relay system. This proposal is in accordance with the generally accepted view that loop closures separate the bulk water from the reaction region (24,29,30). In such models, water is either squeezed out of the active site, or a limited number of selected water molecules are retained for catalysis.…”
Section: Discussionsupporting
confidence: 86%
“…Removal of the 3-4 loop in streptavidin results in a reduction of the K a by 6 orders of magnitude from wild type, nearly half of the binding energy. 16,36 Molecular dynamics, and separate electrostatic and van der Waals free-energy calculations of the biotin-streptavidin complex suggested that the largest contribution to the extremely negative free energy of binding is the non-polar van der Waals contribution of the tryptophan residues Trp 79, Trp 92, Trp 108, and Trp 120 rather than electrostatic forces. 24,25 The simulations also predict a large electrostatic contribution inside the protein, supported by sitedirected mutagenesis experiments studies on streptavidin, which show that mutation of a residue directly hydrogen-bonded to the ureido moiety of biotin results in a substantial decrease in binding energy.…”
Section: Introductionmentioning
confidence: 99%